Impact of Innovated Per Adult Human Unit Method (PAHUM) vs. Error Bound Per Capita (PC): Recalibration of EU and Developing Countries (India), Family/ Households’ Population, Food Security and Environmental Sustainability - Sumer Hasimoglu (Challenging Issues on Environment and Earth Science Vol. 5, 2021)
UNSDGs (UN Sustainable Development Goals, especially SDG2) agenda & Communication of Lisbon Strategy of EU sets out an integrated package of measures to deliver more sustainable consumption (Including food), better environmental protection and correct population, production/consumption evaluations (i.e., cereal) by using appropriate and more meaningful methods, UNITS that are necessary. Observations and findings indicate lack of harmonization of definitions & regulations concerning how data are obtained & method/criteria/UNIT (i.e., PC, AE) presented further complicate the combination & comparison of data from different countries & regions including family/household evaluations. Failure to recognize & address the problems inherent to error bound PC (19.4 percentage unit error), “one-size-fits-all accept or reject” approach in food (organic/conventional) & other goods consumption calculations & projections of the target populations (which are easy to use) may result in erroneous production & consumption plus CO2 emission projections. A radical evaluation method change in global organic/conventional food systems is needed to meet the above challenges. The state of the art of innovated PAHUM or Age and Gender Corrected Per Capita (PCagc) (Copyright©1989-USA) is to evaluate demographic structure, consumer & present/future food (Cereal) consumption potential of EU28 and developing countries. PAHUM focuses on research with systems approach, contributing to the development of tomorrow’s food systems including CO2 emissions-biodiversity relations & also focuses on the unforeseen consequences of PC cereal (grain) consumption/production evaluations & compare of families, households of developed & developing countries. PAHUM evaluation indicated that on PC bases we are overestimating the major food (Cereal) consumption/production projections. We have to think & ask questions about continuous use error bound PC – metric evaluations & how badly the evaluations will change the future planning of the decision makers.